'Mode 3' universities and academic firms: thinking beyond the box trans-disciplinarity and nonlinear innovation dynamics within coopetitive entrepreneurial ecosystems. (2018) - Carayannis, Elias G.; Grigoroudis, Evangelos; Campbell, David F.J.; Meissner, Dirk; Stamati, Dimitra
The main objective of the paper is to examine if 'Mode 3' universities represent a new and advanced type of an entrepreneurial university, perhaps transcending the entrepreneurial university, and identify the specific characteristics of 'Mode 3' universities. According to its definition, a 'Mode 3' university represents a type of organisation capable of higher order learning and in this regard a type of open, highly complex, and non-linear knowledge production system that seeks and realises creative ways of combining, recombining, and integrating different principles of knowledge production and knowledge application (e.g., 'Mode 1' and 'Mode 2'). Thus, 'Mode 3' universities clearly encourage diversity and heterogeneity, while they emphasise and engender creative and innovative organisational contexts for research, education, and innovation. Several examples are offered in this context in order to demonstrate how and why the concept of 'Mode 3' universities is better endowed for addressing the current and future challenges compared to a simple 'entrepreneurial university' approach. The full exploration of 'Mode 3' universities furthermore demands a strong linkage and contextualisation with (entrepreneurial) ecosystems.